Charakterystyka zmian ściśliwości roztworów soli NaCl pod wpływem wysokich ciśnień hydrostatycznych - Koszela-Marek, Ewa (Wydawnictwa AGH, 2009)
The paper presents results of changes in compressibility of water and salt NaCl solutions of concentrations 5, 10, 20 $g/dm^{3}$ under high hydrostatic pressure from 50 up to 400 MPa in 21 degrees of Celsius. Special apparatus was used by compressibility researches - the high-pressure research position. Compressibility for NaCl water solutions evolved non-linearly. A clear relation appeared between changes in the volume of NaCl solutions, and the size of operating pressure. Reaction is also visible between compressibility and the size of concentration of the researched solution. The biggest change in volume (8.96%) appeared by the solution with the smallest concentration (5 $g/dm^{3}$), under the biggest pressure (400 MPa). The smallest change in volume (1.62%) was noted for solution with the biggest concentration (20 $g/dm^{3}$), under the smallest pressure (50 MPa).

Artykuł przedstawia wyniki zmian ściśliwości wodnych roztworów soli NaCl o stężeniach 5, 10, 20 $g/dm^{3}$ pod wpływem działania wysokich ciśnień hydrostatycznych od 50 do 400 MPa, w temperaturze 21stopni Celsjusza. Badania ściśliwości przeprowadzono wykorzystując specjalną aparaturę: wysokociśnieniowe stanowisko badawcze. Współczynniki ściśliwości [symbol] dla wodnych roztworów NaCl ulegały zmianom nieliniowym. Zaznaczyła się wyraźna zależność między zmianami objętości roztworów NaCI i wielkością działającego ciśnienia. Widać również zależność ściśliwości od wielkości stężenia badanych roztworów. Największa zmiana objętości (8,96 %) nastąpiła dla roztworu o stężeniu najmniejszym (5 $g/dm^{3}$), przy ciśnieniu największym (400 MPa). Najmniejszą zmianę objętości zanotowano (1,62%) dla roztworu o stężeniu największym (20 $g/dm^{3}$), przy najmniejszym ciśnieniu (50 MPa).
Characteristics of NaCl solutions compressibility changes under high hydrostatic pressures
Górnictwo i Geoinżynieria
Bibliogr. s. 367.
Keywords: compressibility; ściśliwość; salt solutions; roztwory soli; high hydrostatic pressures; wysokie ciśnienie hydrostatyczne